Language Features for Access Control - Ancilotti, P.; Boari, M.; Lijtmaer, N. (IEEE transactions on software engineering, 1983)
The properties of a capability-based protection mechanism to be incorporated in a language for concurrent programming are presented. The protection mechanism is first abstractly characterized in terms of a protection model; the components of the protection mechanism, that is, the objects, subjects, and protection rules which govern the accessing to the objects by the subjects, are defined.